Gender Stereotype Portrayal on Hardworking Women In “The Intern” Movie Director’s Perspective - Rifqi, Muhammad; Prastiwi, Yeni (Language Circle: Journal of Language and Literature, 2024)
As the film industry developed, movies became a concern for some people. One of them is feminists, feminists are starting to infiltrate the film world, and like actors and directors, like Nancy Meyers, Nancy is a gender equality person. The purpose of this research is to find similarities between the characters in the film The Intern (Jules Ostin) character and the director and the reasons why the director included those elements. This research uses a qualitative descriptive method and the sources are the film itself (The Intern 2015), transcripts from the film and news media. Based on the results of this study, it can be concluded that there are similarities between the life of the director and the character of Jules Ostin. The director tries to include and portray several elements of feminism and gender stereotypes that are presented through the director’s own biography, and also emphasizes that the director (Nancy Meyers) wants people and views to notice a woman when she brings this subject in the film to change and consider them equal to men. in matters of life or choosing a profession.